Examining Calamity Through Microscopic Lens: Nature of Tsunami and its Disaster Management Plan. - Bhoi, Panchanan and Sahay, Ashok K. (2006)
The nature’s fury in the form of tsunami had plunged the southern costal areas of India in shock and grief. Though India has progressed substantially in the field of science and technology, this was of little help in escaping the colossal loss suffered across the region. Our geologists and meteorological officials did not even find a remote clue to the disaster in waiting. A tsunami might have not been able to predict, but the probability of dangerous tides need not have been ignored. In this context, the prime objective of this paper is to stimulate a multidisciplinary discussion on problems associated with tsunami and suggests a plan for protecting people and property. Further it stresses that if people are made people aware of what to do before and after a disaster hits, this can significantly reduce disaster impact and property damage.